2020
DOI: 10.5812/ijcm.105799
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Basal Cell Carcinoma After Mohs Micrographic Surgery: A 4-Year Retrospective Analysis

Abstract: Background: Among non-melanoma skin cancers (NMSC), Basal cell carcinoma (BCC) is one of the most common. Objectives: We endeavored to assess the recurrence rate of BCC after surgery and compare tumors recurrence based on different aspects. Methods: This was a retrospective and observational study which was analyzed medical records of 154 patients who had Mohs micrographic surgery (MMS) from March 2013 to February 2017 in two clinical centers. For finding if the clinical characteristics of the patients have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The rate of recurrence in our retrospective review of the chart was 19.38%, which is consistent with studies conducted in Sweden, Turkey, the Netherlands, and the United Kingdom [ 8 , 20 - 22 ]. According to our audit, the nodular type is the most commonly prevalent type of basal cell carcinoma in our population, which is consistent with the results of audits conducted in other studies except Elis Salimi et al [ 23 ], who concluded that the infiltrating type is the most common in their region. The most common region involved in basal cell carcinoma is the head and neck, which is in concurrence with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of recurrence in our retrospective review of the chart was 19.38%, which is consistent with studies conducted in Sweden, Turkey, the Netherlands, and the United Kingdom [ 8 , 20 - 22 ]. According to our audit, the nodular type is the most commonly prevalent type of basal cell carcinoma in our population, which is consistent with the results of audits conducted in other studies except Elis Salimi et al [ 23 ], who concluded that the infiltrating type is the most common in their region. The most common region involved in basal cell carcinoma is the head and neck, which is in concurrence with our findings.…”
Section: Discussionsupporting
confidence: 92%